Clonal immunoglobulin λ light‐chain gene rearrangements detected by next generation sequencing in POEMS syndrome. Issue 9 (31st August 2018) - Kawajiri‐Manako, Chika; Mimura, Naoya; Fukuyo, Masaki; Namba, Hiroe; Rahmutulla, Bahityar; Nagao, Yuhei; Togasaki, Emi; Shimizu, Ryoh; Oshima‐Hasegawa, Nagisa; Tsukamoto, Shokichi; Mitsukawa, Shio; Takeda, Yusuke; et al.
Abstract : Polyneuropathy, organomegaly, endocrinopathy, M‐protein, and skin changes (POEMS) syndrome is a rare plasma cell dyscrasia characterized by polyneuropathy, organomegaly, endocrinopathy, extravascular fluid overload, M protein, and a myriad of skin changes. The pathogenesis is poorly understood, but monoclonal plasma cells are λ‐restricted and these immunoglobulin λ light chain variable (IGLV) region genes are derived from only two germlines, either IGLV1‐44 or 1‐40 . Here we analyzed the clonal IGLV gene rearrangements of genomic DNA samples of bone marrow mononuclear cells using next‐generation sequencing (NGS) to understand the clonal composition of IGLV genes in patients with POEMS syndrome (n = 30). The dominant IGLV gene rearrangement of POEMS syndrome‐specific germline sequences were significantly increased in 11 POEMS patients (36.7%; IGLV1‐44 : n = 9, IGLV1‐40 : n = 2). In some cases, IGLV gene rearrangement clone was not detected as significant increase but was detected using cDNA samples by heteroduplex (HD) analysis and Sanger sequencing, suggesting that the quite small number of monoclonal plasma cells may produce large quantity of mRNA of monoclonal proteins. However, significant increase of dominant clone sizes was not directly linked to the initial disease status. On the other hand, in cases with significantly increased dominant clones, they decreased and increased accompanying with disease remission and relapse. These data demonstrate that monoclonal plasma cells are related to the pathogenesis of POEMS syndrome.